2015
DOI: 10.1021/acs.inorgchem.5b00322
|View full text |Cite
|
Sign up to set email alerts
|

Ionothermal Syntheses of Nano- and Microstructured Ternary Copper–Indium–Chalcogenides

Abstract: Ternary compounds of copper indium selenide nano-and microsized materials were prepared through colloidal synthesis using an indium(III) selenide precursor and copper(I) chloride via a microwave-assisted ionothermal route. The indium-(III) selenide precursor used in the reaction was formed in situ from a diphenyl diselenide precursor and chloroindate(III) ionic liquids (ILs), also via a microwave-assisted ionothermal route. The crystal structures of three intermediates, namely, CuCl 2 (OMe) 2 -(H 2 O)){Cu(PhSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The binary compounds or their molecular precursors can be employed as starting materials for the preparation of ternary compounds of type CuInE 2 . The chalcopyrite type compound CuInSe 2 has been well established as the key semiconducting material for making the next generation PV devices due to their favorable properties such as high absorption coefficient, good radiation and thermal stability, high photovoltaic efficiency and low toxicity ,. Various methods to synthesize such material have been reported, however only a few have been used to generate thin film or nano‐material of CuInSe 2 with desired properties ,.…”
Section: Introductionmentioning
confidence: 99%
“…The binary compounds or their molecular precursors can be employed as starting materials for the preparation of ternary compounds of type CuInE 2 . The chalcopyrite type compound CuInSe 2 has been well established as the key semiconducting material for making the next generation PV devices due to their favorable properties such as high absorption coefficient, good radiation and thermal stability, high photovoltaic efficiency and low toxicity ,. Various methods to synthesize such material have been reported, however only a few have been used to generate thin film or nano‐material of CuInSe 2 with desired properties ,.…”
Section: Introductionmentioning
confidence: 99%
“…[45] Other types of discrete metal chalcogenide clusters have also been documented. [19,49,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] All the discrete supertetrahedral Tn chalcogenido clusters synthesized in ILs thus far are summarized in Table 1, and the space group, band gap and synthetic conditions are listed as well. Noticeably, [Bmmim]Cl (Figure 2, left; Bmmim = 1-butyl-2,3-dimethylimidazolium) was widely adopted in the synthetic process.…”
Section: Syntheses and Structures Of Discrete Chalcogenido Tn Clustermentioning
confidence: 99%
“…The syntheses of discrete supertetrahedral T n chalcogenido clusters, however, were still elusive until we firstly reported on the syntheses of T5 clusters in ILs [45] . Other types of discrete metal chalcogenide clusters have also been documented [19,49,64–78] …”
Section: Syntheses and Structures Of Discrete Chalcogenido Tn Clustersmentioning
confidence: 99%
“…It is a powerful tool for the synthesis of the nanostructured materials due to the advantageous properties of rapidity and reduced energy consumption. Much progress on the preparation of nanomaterials by using this rapid method has been published, such as metal oxides (Schütz et al 2017), metal sulfides (Ma et al 2014), metal selenides (Tyrrell et al 2015), metal tellurides (Schaumann et al 2017), etc. A previous study revealed that ionic liquids have obvious effects on both the crystal structure and morphology of the nanomaterials (Lin et al 2017).…”
Section: Introductionmentioning
confidence: 99%